International norms on the trade of halal food : conflicts and prospect of harmonization - Syazatul Akhyar binti Saifulyazan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
At present, halal certification is not common practice. As a result, halal certification has become one of the most sought-after sectors in the global economy. The expansion of halal markets across the globe has driven both Muslims and non-Muslims countries to invest substantially in the development of their own halal certification system. The lack of a unified global halal standard has made the halal industry more competitive in terms of pushing forward technical standards alongside halal food products. Consequently, the halal legal framework in Malaysia has experienced constant developments and amendments since the 1970s as Malaysia, one of the leading forces in that halal industry, has been protecting the integrity of the halal industry through enforcing various laws and regulations. Although these laws are mainly meant for local execution, some of the rules and regulations are designed for imported products. In the meantime, halal certification in Malaysia is compulsory for imported meat poultry and their derivatives products. On the other hand, halal certification for locally made food products is a voluntary undertaking. Such measure is crucial to protect the Muslim consumers against deceptive practices as it is viewed that the lack of labelling will make tracing and monitoring difficult. The compulsory halal certification for imported meat and poultry is perceived as an unjustifiable restriction by some importers, including the United States of America. It is alleged that these restrictions are some forms of non-tariff trade barriers which are inconsistent with the principles and rules of the World Trade Organization (WTO). It is also argued that the Malaysian halal certification process goes beyond what prescribed by the Codex Alimentarius guidelines. In this paper, although Malaysian halal import rules have not been brought upon the contemplation of the WTO Dispute Settlement Body (DSB), the WTO's decisions on two Indonesian trade disputes relating to its halal certification measures are examined. This study took into account the perspectives of Malaysian agencies responsible for halal monitoring. This is to understand the implication of Indonesian trade disputes' decisions towards the Malaysian halal certification scheme through semi-structured interviews. The outcome of this research can be used as arguments to defend the Malaysian halal certification measure for imported meat and poultry. In addition, this study proposes several recommendations for the improvement of both local and international halal standard and guidelines. From the findings, it can be concluded that halal certification should not be perceived as a form of technical barriers to trade as it is necessary to protect Muslim consumers against deceptive practices.